Preparation of cerium titanate brannerite by solution combustion, and phase transformation during heat treatment. Issue 5 (May 2017) - Kong, Linggen; Gregg, Daniel J.; Vance, Eric R.; Karatchevtseva, Inna; Lumpkin, Gregory R.; Blackford, Mark G.; Holmes, Rohan; Jovanovic, Miodrag; Triani, Gerry
Abstract: An aqueous solution route was employed to prepare cerium titanate oxide brannerite. Thermal analysis, X-ray diffraction, Raman spectroscopy, transmission and scanning electron spectroscopy, were used to investigate the brannerite structure formation and bulk properties. Mixed metal oxides (TiO2, CeO2 and brannerite CeTi2 O6 ) were formed upon calcination at 800 °C for 12 h. The amount of brannerite phase decreased to form the constituent oxides with increasing calcination temperature and only pure TiO2 and CeO2 were present after 1200 °C calcination. The brannerite CeTi2 O6 phase reformed at 1300 °C, and its relative amount was increased with dwell time. After 48 h calcination at 1300 °C, brannerite with only minor metal oxide impurities (<1%) was observed. The sample melted at 1400 °C which led to the collapse of brannerite back to its constituent oxides. Further, the phase formation was influenced by pelletization of the powders, which may be explained by a molar volume increase during brannerite formation. Attempts to confirm this hypothesis using Pu brannerite were inconclusive.